PERAN PEMERINTAH DESA DALAM PENYEDIAAN AIR BERSIH PADA MASYARAKAT PESISIR LOMBOK TIMUR - SALMI AINI (Universitas Hamzanwadi, 2019)
The Role of Village Government in Provision of Clean Water in Coastal Communities in Kedome Hamlet, Ketapang Raya Village, Keruak Distrct, East Lombok Regency. This study aims to derermine the role of village government in providing clean to coastal communities, East Lombok Regency. The formulation of the problem in this study is: what is the role of the village government in providing clean water to costal communities in kedome Village, East Lombok Regency. This type of research uses descriptive qualitative research methods and strucural approaches. The. The techniques used in analyzing data are in three stages, including : data reduction, data presentation, and conclussion drawing. Based on the results of this study indicate that, the village goverment has a role in the provision of clean water. So far the village government has carriend out its role but it still not maximized due to the implementation of clean water in coastal communities that have not been evenly realized for each house. The village government is unabel to work alone in carrying out its role, it involves all parties involved in the provision of cleam water, both from the central government, village government hamcommunities.